Morphological identification of weevil and fungal pathogen associated with sweet potato tuber during storage - Nur Aida H.,; Mohammad Zarith Z.,; Siti Nor Shuhada A.,; Khadijah S.,; Basari N.,; Shamsul Bahri A.R.,; Nurul Faziha I., (Penerbit Universiti Kebangsaan Malaysia, 2017)
Sweet potato is a perishable food crop that is prone to weevil and fungal infection. Development of diseases due to fungal infection will lower its quality, reduce marketable price and sometimes the tubers are unable to sell. Crop losses due to diseases not only have bad implication to farmers, but also give threat to global food production and food security. This study was conducted to identify and document the insect and fungal pathogens associated with sweet potato diseases. For this purpose, infected tubers were collected, incubated and isolated before conducting the pathogenicity test. Ninety sweet potato weevils, Cylas formicarius had emerged and caused extensive damaged to the tuber. Following the sweet potato weevil infestation, four fungal isolates were successfully identified as Fusarium oxysporum (one isolate), Penicillium sp. (one isolate) and Aspergillus sp. (two isolates). All these isolates were pathogenic to sweet potato tubers with different level of diseases severity, ranged from 33.33% to 42.59%. Identification of weevil and fungal pathogen associated with sweet potato diseases is important to help in control strategy to avoid epidemic diseases that may cause loss of economic return. Besides that, farmers should applied integrated pest management control for continuous production of good quality sweet potato tuber.